A C18 Quaternary Ammonium Library. Issue 21 (27th December 2016) - Porosa, Lukasz; Deng, Hellen; Bedard, Joseph; Lough, Alan J.; Wolfaardt, Gideon; Foucher, Daniel A.
Abstract: A library of precursor and functionally active quaternary ammonium cations (QACs) for use as corrosion resistant and or antimicrobial coatings, or alternatively as polymer modifiers, is described. High yielding and improved routes to a series of functionally terminated allyl ([(CH2 =CH‐CH2 )m ‐N + (Me)n ‐C18 H37 ][X − ], 1 : m=1, n=2, X − =Br −, 3 : m=2, n=1, X − =I −, 4 : m=3, n=0, X − =Br − ) vinyl ([CH2 =CHCH2 CH2 ‐N + Me2 ‐C18 H37 ][Br − ]5 ), hydroxy ([HO‐(CH2 )m ‐N + Me2 ‐C18 H37 ][Br − ], 6 : m=3, 7 : m=4), haloalkyl ([X 1 ‐(CH2 )3 ‐N + Me2 ‐C18 H37 ][X − ]8 : X 1 =Br, X=Br −, 9 : X 1 =Cl, X=I − ), dimethoxyphenethyl ([(MeO)2 C6 H3 (CH2 )2 ‐N + Me2 ‐C18 H37 ][Br − ], 11 ), acetamido ([H3 C(O)NH‐(CH2 )3 ‐N + Me2 ‐C18 H37 ][Cl − ], 12 ) cyano ([N≡C–CH2 ‐N + Me2 ‐C18 H37 ][Cl − ], 13 ), organocarbonylamino ([R‐C(O)2 NH‐(CH2 )3 ‐N + Me2 ‐C18 H37 ][Br − ], 14 : R= t ‐Bu‐, 15 : R=PhCH2 ‐), phthalimido ([PhthN‐(CH2 )3 ‐N + Me2 ‐C18 H37 ][Br − ], 16 ), amino ([H2 N‐(CH2 )3 ‐N + Me2 ‐C18 H37 ][Br − ]17 ), acetylthio ([HC(O)S‐(CH2 )3 ‐N + Me2 ‐C18 H37 ][Cl − ], 18 ), thiol ([HS‐(CH2 )3 ‐N + Me2 ‐C18 H37 ][Cl − ]19 ), disulfa ([‐S‐(CH2 )2 ‐N + Me2 ‐C18 H37 ]2 [Br − ]2, 20 ) C18 QACs prepared by thermal and or microwave driven Menshutkin reactions are detailed. All new compounds were characterized by NMR spectroscopy, HRMS spectrometry and in the case of1 and6 by X‐ray crystallography. Abstract : A series of thiol, vinyl, catechol, halo, amine and hydroxy containing precursor and functional active C18 quaternary ammonium salts prepared by new or improved synthetic routes is described. These C18 containing materials can be used as corrosion inhibitors, antimicrobials and polymer modifiers.